Antiviral Potential of Curcumin in Mitigating COVID-19 Effects and Post-COVID-19 Sequelae - Athira, T. R.; Jisha, K. C. (Current Botany, 2025)
COVID-19 is a respiratory disease resulting from infection with the Severe Acute Respiratory Syndrome Coronavirus Type 2 (SARS-CoV-2) virus, which may manifest as mild, moderate, or severe symptoms. Even after recovering from the disease, some individuals may experience persistent symptoms, known as “long COVID”. Curcumin, a polyphenol extracted from Curcuma longa L., exhibits diverse medicinal properties including antiviral, anti-inflammatory, anti-thrombotic, antioxidant, antiproliferative, and immunomodulatory effects. It can potentially be a therapeutic agent for treating COVID-19 due to its ability to modulate the immune response and inhibit cytokine storms. These actions can help prevent severe difficulties like acute respiratory distress syndrome (ARDS) and multiorgan failure. Curcumin specifically targets viral entry, replication, and the molecular signalling cascade responsible for pathophysiological effects, making it a potential option for combating COVID-19 and addressing its long-term post-COVID effects on health. Using nanocarriers can overcome the limitations of curcumin’s poor bioavailability and solubility, allowing for more effective delivery to the target cells and tissues.